Teachers' perceptions regarding school principals' coaching skills - Yirci, Ramazan; Ozdemir, Tuncay Yavuz; Kartal, Secil Eda; Kocabas, Ibrahim (Routledge Journals, Taylor & Francis Ltd, 2014)
The purpose of this study was to find out teachers' perceptions about school principals' coaching skills. The study was carried out within qualitative research methods. The study group included 76 teachers in Elazig and 73 teachers in Kahramanmaras provinces of Turkey. All the data were processed using Nvivo 9 software. The results indicate that teachers' perceptions about their principals' coaching skills do not differ according to the age, marital status, sex and education status variables. The teachers think that their principals are successful at some coaching skills such as being experienced and knowledgeable, being an effective listener and setting achievable targets. Principals fail to show empathy, communicate effectively, praise, give feedback, motivate and have effective inquiry coaching skills. According to teachers' opinions, being a role model, showing empathy, praising, effectively communicating and motivating are important coaching skills that they would show if they were to sit in the principal chair.
Keywords: coaching; coaching skills; school principal; school management